Circular RNA S-7 promotes ovarian cancer EMT via sponging miR-641 to up-regulate ZEB1 and MDM2. Issue 7 (24th July 2020) - Zhang, Fenghua; Xu, Yun; Ye, Wenfeng; Jiang, Jingting; Wu, Changping
Abstract: Background: Ovarian cancer (OC) is one lethal gynecologic cancer, with a 5-year survival rate approximately 47% and localized stage diagnosis of 15%. Circular RNAs are promising biomarkers for malignancies. Methods: CiRS-7 expression was confirmed in 40 paired OC and normal adjacent tissues from 40 OC patients with different TNM stages, lymph node metastasis status and overall survival rate, also 5 different OC cell lines by qRT-PCR. Effects of ciRS-7 silence on OC cell phenotypes were determined in OC cells and Xenograft mouse model. StarBase was used to predict binding sites between ciRS-7 and micRNAs. Pearson correlation analysis and RNA-immunoprecipitation assay were used to determine the association between genes. Point mutation and rescue experiments were applied for molecular mechanism investigation. Results: CiRS-7 expression was significantly higher in OC cells and tissues, which was significantly associated with the TNM stages, lymph node metastasis status and overall survival rate in OC patients. CiRS-7 silence inhibited OC cell growth and metastasis. CiRS-7 sponged miR-641 to up-regulate ZEB1 and MDM2 expression in OC development. Conclusion: CiRS-7 serves as a competing endogenous RNA of miR-641 that promoted cell growth and metastasis in OC, via regulating ZEB1 and MDM2-mediated EMT. High ciRS-7 expression was a poor prognosis of TNM stages, lymph node metastasis status and overall survival rate in OC patients. Targeting ciRS-7/miR-641/ZEB1 or ciRS-7/miR-641/MDM2 axis may be a novel diagnostic, prognostic and therapeutic strategy for OC.